Delineating Crosstalk Mechanisms of the Ubiquitin Proteasome System That Regulate Apoptosis - Gupta, Ishita; Singh, Kanika; Varshney, Nishant K.; Khan, Sameena (Frontiers in Cell and Developmental Biology, 2018)
Regulatory functions of the ubiquitin-proteasome system (UPS) are exercised mainly by the ubiquitin ligases and deubiquitinating enzymes. Degradation of apoptotic proteins by UPS is central to the maintenance of cell health, and deregulation of this process is associated with several diseases including tumors, neurodegenerative disorders, diabetes, and inflammation. Therefore, it is the view that interrogating protein turnover in cells can offer a strategy for delineating disease-causing mechanistic perturbations and facilitate identification of drug targets¬¬. In this review, we are summarizing an overview to elucidate the updated knowledge on the molecular interplay between the apoptosis and UPS pathways. We have condensed around 100 enzymes of UPS machinery from the literature that ubiquitinates or deubiquitinates the apoptotic proteins and regulates the cell fate. We have also provided a detailed insight into how the UPS proteins are able to fine-tune the intrinsic, extrinsic and p53-mediated apoptotic pathways to regulate cell survival or cell death. This review provides a comprehensive overview of the potential of UPS players as a drug target for cancer and other human disorders.